Adidas AG valuation: Buy, hold or sell? - Duarte, Cátia Sofia Gomes (2021)
Adidas, AG. is the second world’s leading player in the sportswear industry, a well-known company for its strong financial performance and solid representativeness within a booming and fierce industry. Notwithstanding, the group is currently going through a controversial phase with Reebok divestiture while, simultaneously, tries to adapt its business to a pandemic reality. Thus, it is important to analyze if the market is accurately pricing the future prospects/challenges into Adidas’ stock price or if this could be an investment opportunity. The main purpose of this master thesis is to estimate Adidas’ fair price as of 31st December of 2020 and compare it with the market price to produce an investment recommendation of either sell, buy or hold. Hence, several valuation methodologies were applied: The Free Cash Flow to the Firm, the Free Cash Flow to the Equity, the Economic Value-Added model, and Relative Valuation. All assumptions applied to the valuation models follow a conservative approach and are supported by historical, macroeconomic, and industry data. Based on the results of the different valuation methodologies, a share price range of €329.3 – €340.4 was established, implying an upside potential of 11% – 14%. Therefore, it is concluded that Adidas was undervalued, and a buy recommendation was issued for potential investors. Subsequently, sensitivity analysis, a monte carlo simulation and a comparison to an equity research note issued by J.P. Morgan were performed to increase the robustness of this equity valuation results.